2020
DOI: 10.1177/1044207320920004
|View full text |Cite
|
Sign up to set email alerts
|

Policy, Preparation, and Practice . . . Oh My! Current Policy Regarding the Paraprofessional Role and Preparation for Working With Students With Disabilities

Abstract: Over the past two decades, the paraprofessional role has expanded to include a variety of support roles in both general and special education. Although the most recent 2004 reauthorization of the Individuals with Disabilities Education Act (IDEA) addressed the necessity of paraprofessional preparation, training, and supervision, the field of education continues to struggle with incorporating these necessary components. In this article, we summarize current policies and standards, both state and federal, for tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
(37 reference statements)
0
6
0
Order By: Relevance
“…This is important to understand as policymakers and administrators think about how they may leverage this source of support in providing students, both SWDs and general education students, with the resources they need to be successful. As previous research has established, the training of paraprofessionals is not at all standardized across the nation (Breton, 2010;Massafra et al, 2020), yet paraprofessionals themselves state that they are involved in many aspects of the school day, especially with SWDs (Liston et al, 2009) and that their training is lacking in key areas (Breton, 2010). Our study shows that an increase in paraprofessional presence is occurring in classrooms with SWDs, and we recommend that policymakers address the lack of training and preparation for this group of educators.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is important to understand as policymakers and administrators think about how they may leverage this source of support in providing students, both SWDs and general education students, with the resources they need to be successful. As previous research has established, the training of paraprofessionals is not at all standardized across the nation (Breton, 2010;Massafra et al, 2020), yet paraprofessionals themselves state that they are involved in many aspects of the school day, especially with SWDs (Liston et al, 2009) and that their training is lacking in key areas (Breton, 2010). Our study shows that an increase in paraprofessional presence is occurring in classrooms with SWDs, and we recommend that policymakers address the lack of training and preparation for this group of educators.…”
Section: Discussionmentioning
confidence: 99%
“…A 2020 study by Massafra, Gershwin, and Gosselin explores the current state of affairs for paraprofessionals in terms of their responsibilities and the way states are providing frameworks for adequate training. The authors describe that while the applicable federal policies do set some parameters on the role of paraprofessionals, in reality, their responsibilities can vary widely and with each state setting its own implementation of these federal definitions and corresponding training (Massafra et al, 2020).…”
Section: The Role Of Paraprofessionalsmentioning
confidence: 99%
“…Providing training and support for paraprofessionals to implement peer network interventions may be a valuable way to use paraprofessional support to improve social-related outcomes for students with IDD. However, we would emphasize that paraprofessionals are far too often tasked with providing supports to students with IDD without the support, collaboration, and supervision that they need and that is required by law (Biggs et al, 2016; Massafra et al, 2020). Paraprofessional implementation should be supported by close collaboration and supervision from others on the educational team, such as special education teachers.…”
Section: Discussionmentioning
confidence: 99%
“…far too often tasked with providing supports to students with IDD without the support, collaboration, and supervision that they need and that is required by law (Biggs et al, 2016;Massafra et al, 2020). Paraprofessional implementation should be supported by close collaboration and supervision from others on the educational team, such as special education teachers.…”
Section: Declaration Of Conflicting Interestsmentioning
confidence: 99%
“…Although federal law requires training and professional development for paraeducators, the detailed review of state requirements by Massafra et al (2020) revealed that 43 states do not require initial training and 40 states do not have provisions for ongoing professional development. When training is provided, the most frequent type of training tends to be one-time workshops without follow-up coaching (Walker et al, 2020), which is commonly acknowledged as a professional development method that does not lead to use of strategies with fidelity (Hall et al, 2010).…”
mentioning
confidence: 99%